Low-velocity impact to transmission line conductors. (August 2017) - Waters, Daniel H.; Hoffman, Joseph; Hakansson, Eva; Kumosa, Maciej
Highlights: A unique approach to impact testing of transmission line conductors is proposed. With unconstrained ends, conductors failed by rod collapse. With axial tension, stable conductor response was observed. A simplified FEM model was proposed and verified under static conditions. Dynamic impact predictions were less accurate. Abstract: This combined experimental and numerical study addresses mechanical effects associated with the energy dissipation from transverse low-velocity impacts on a novel High Temperature Low Sag (HTLS) transmission line conductor, subjected to either free or constrained end conditions and large axial tensile loads. Impact experiments were conducted on one type of Polymer Composite Core Conductor (PCCC) belonging to the family of HTLS designs. The experimental work performed using an original approach was supported by non-linear static and dynamic finite element analysis. Despite their geometrical simplicity, the numerical models provided useful information regarding the response of the conductor to both static and dynamic conditions. Most importantly it has been determined that the PCCC exhibits good resistance to impact under constrained end conditions with and without initial axial tension. It was also identified that the most damaging condition under impact is when the conductor had free ends and was thus subjected to severe bending. It has been shown in this work that the suggested approach to the impact testing of transmission lines could result in useful predictions of their structural integrity after low-velocity impact either during installation or in service.